2012
DOI: 10.1002/jctb.3695
|View full text |Cite
|
Sign up to set email alerts
|

Alkali pretreatment of softwood spruce and hardwood birch by NaOH/thiourea, NaOH/urea, NaOH/urea/thiourea, and NaOH/PEG to improve ethanol and biogas production

Abstract: Alkali-dissolution pretreatment of softwood spruce and hardwood birch to improve ethanol and biogas production was investigated. The pretreatments were carried out at different temperatures between −15 and 80• C with NaOH/thiourea (7/5.5 wt%), NaOH/urea (7/12 wt%), NaOH/urea/thiourea (7/8/6.5 wt%), and NaOH/PEG (7/1 wt%) aqueous solutions. The pretreated materials were then subjected to enzymatic hydrolysis for 72 h. The pretreatments by NaOH/thiourea at −15• C improved the hydrolysis yields of spruce from 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 20 publications
4
31
0
2
Order By: Relevance
“…Based on the glucose content obtained using the maximum yield for enzymatic saccharification through this biotechnological process, the percentage of bioethanol obtained as 90.19% (converted to theoretical values) indicates possibility of producing 80 L of bioethanol per dry ton of woody biomass. This result lies within the range obtained for wood (28 to 120 L ethanol/ton woody biomass) as reported by various authors using similar pretreatment technologies: dilute acid, alkali, and steam explosion (Mirahmadi et al, 2010;Mohsenzadeh et al, 2012). The pretreatment of lignocellulosic biomass is a determinant stage in the synthesis of biofuels, thus further studies should explore the various pretreatment processes in order to choose the one that best fit the structure of the substrate.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the glucose content obtained using the maximum yield for enzymatic saccharification through this biotechnological process, the percentage of bioethanol obtained as 90.19% (converted to theoretical values) indicates possibility of producing 80 L of bioethanol per dry ton of woody biomass. This result lies within the range obtained for wood (28 to 120 L ethanol/ton woody biomass) as reported by various authors using similar pretreatment technologies: dilute acid, alkali, and steam explosion (Mirahmadi et al, 2010;Mohsenzadeh et al, 2012). The pretreatment of lignocellulosic biomass is a determinant stage in the synthesis of biofuels, thus further studies should explore the various pretreatment processes in order to choose the one that best fit the structure of the substrate.…”
Section: Discussionsupporting
confidence: 86%
“…Alkaline pretreatment is one of the most promising chemical processes which can effectively facilitate further processes. Alkaline pretreatment using sodium hydroxide was frequently applied for softwoods, hardwoods, and agricultural residues to improve ethanol yield and showed promising results (Goshadrou et al, 2011;Mirahmadi et al, 2010;Mohsenzadeh et al, 2011;Nieves et al, 2011;Salehi et al, 2012;Salehian and Karimi, 2013). Sodium hydroxide pretreatment resulted in lignin removal, biomass swelling, more surface reactive functional groups like hydroxyl groups, and surface roughness improvement in the pretreated substrate (Islam et al, 2012;Teghammar et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…An increase in the ethanol production from 30.0% to 80% was observed during alkaline pretreatment. Shafiei et al (2010) and Mohsinzadeh et al (2011) also reported in their studies, that the chemical hydrolysis of biomass yield was greater with alkaline pretreatment at high temperature and residence time [46,47]. Furthermore, the purity of bioethanol from 10.1 ± 0.2%e85% was observed using three step distillations during purification process.…”
Section: Characterization Of Ethanolmentioning
confidence: 84%